Gender difference in the associations of childhood maltreatment and non-suicidal self-injury among adolescents with mood disorders - Yan Yue; Yan Yue; Yi Wang; Ruchang Yang; Ruchang Yang; Feng Zhu; Xuna Yang; Xinchuan Lu; Ping Zhu; Zhengyan Wu; Zhe Li; Xueli Zhao; et al. (Frontiers in Psychiatry, 2023)
BackgroundNon-suicidal self-injury (NSSI) is a common feature among adolescents with mood disorders. Although childhood maltreatment has shown to be associated with non-suicidal self-injury (NSSI), previous studies have yielded mixed results in terms of different subtypes of childhood maltreatment and only few studies have investigated the effects of gender. The present cross-sectional study investigated effects of different types of childhood maltreatment on NSSI, as well as the role of gender in these effects.MethodsIn this cross-sectional study, a total of 142 Chinese adolescent inpatients with mood disorders (37 males and 105 females) were consecutively recruited within a psychiatric hospital. Demographic and clinical characteristics were collected. Participants were administered the Childhood Trauma Questionnaire (CTQ), the Functional Assessment of Self-Mutilation (FASM).Results76.8% of the sample reported engaging NSSI in the previous 12  months. Female participants were more likely to engage in NSSI than males (p < 0.001). Participants in the NSSI group reported significantly more experiences of emotional abuse (p < 0.001) and emotional neglect (p = 0.005). With regards to gender differences, female participants who have experienced emotional abuse were more likely to engage in NSSI (p = 0.03).ConclusionAs a whole, NSSI represents a frequent phenomenon among adolescent clinical populations and females were more likely to engage in NSSI than males. NSSI was significantly related to experiences of childhood maltreatment and specifically related to emotional abuse and emotional neglect over and above other types of childhood maltreatment. Females were more sensitive to emotional abuse than males. Our study highlights the importance of screening for subtypes of childhood maltreatment as well as considering the effects of gender.